Wet-cold forest altitudinal shifts during the Pleistocene-Holocene in the Brazilian central mountain range (Serra do Espinhaço Meridional) - Ingrid Horák-Terra; Antonio Martínez Cortizas; Cynthia Fernandes Pinto da Luz; Kauê Fonseca; Katerine Escobar Torrez; Marie-Pierre Ledru; Fabrício da Silva Terra; Plínio Barbosa de Camargo; Alexandre Christófaro Silva; Pablo Vidal-Torrado; Olalla López-Costas (CATENA, 2026)

First report of free-ranging maned wolf (Chrysocyon brachyurus) coinfected with Dioctophyma renale and Pearsonema sp. in Brazil - Alexandre Carvalho Costa; Elisabeth Neves Mureb; Naiara Vidal Stocco; Ágatha Ferreira Xavier de Oliveira; Bruna Emely Pereira Barbosa; Cristiano Chaves Pessoa da Veiga; Andresa Guimarães; Juliana Macedo Raimundo; Huarrisson Azevedo Santos; Daniel de Almeida Balthazar; Cristiane Divan Baldani (Veterinary Research Communications, 2026)
The manned wolf ( Chrysocyon brachyurus ) has a highly diversified diet, that includes fish and amphibians, which may harbor infective forms of parasites, such as Dioctophyma renale and Pearsonema (syn. Capillaria ) spp. Both parasites affect the urinary tract of their hosts, with D. renale being capable of infecting a wide range of mammalian species, whereas Pearsonema spp. exclusively parasitizes wild and domestic canids and felids, releasing their eggs in the urine of the host. This study reports the first coinfection by D. renale and Pearsonema sp. in the urine of a free-ranging maned wolf as well as associated laboratory findings. A male adult maned wolf, injured in a train accident in an urban area, was referred to the Centro de Triagem de Animais Silvestres (CETAS) – Rio de Janeiro, Brazil, where hemogram, biochemistry, ultrasonography, and urinalysis were performed. Ultrasonography examination revealed findings consistent with parasitism by D. renale in the right kidney and right perirenal region. Urinary sediment examination showed D. renale (5/field) and Pearsonema sp. eggs (1/field). Egg morphometry was performed, yielding mean length and width values of 62.2 μm and 41.2 μm for D. renale and 58.0 μm and 26.1 μm for Pearsonema sp., respectively. Through sediment examination and morphometry, it was possible to confirm Pearsonema sp. and D. renale infection, the latter also confirmed by ultrasonography, highlighting the importance of urinalysis in wild animals and demonstrating the need for continuous investigation into Pearsonema spp. which are poorly studied in wild canids.

Retraction notice to “Spatial and temporal distribution of urban heat islands” [Sci. Total Environ. 605–606 (2017) 946–956] - Alexandre Rosa dos Santos; Felício Santos de Oliveira; Aderbal Gomes da Silva; José Marinaldo Gleriani; Wantuelfer Gonçalves; Giselle Lemos Moreira; Felipe Gimenes Silva; Elvis Ricardo Figueira Branco; Marks Melo Moura; Rosane Gomes da Silva; Ronie Silva Juvanhol; Kaíse Barbosa de Souza; et al. (Science of The Total Environment, 2026)

Assessing responses of reef island seabirds to environmental and anthropogenic drivers - Tristan Berr; Alexandre Millon; Pascal Dumas; Poetea Guehenneuc; Fany Perez; Hélène De Méringo; Julien Baudat‐Franceschi; Éric Vidal (Conservation Biology, 2026)
Tropical insular ecosystems face escalating, cumulative impacts of land‐ and sea‐based ecological threats that jeopardize the long‐term sustainability of their native communities. This joint vulnerability is epitomized by reef island seabirds, which are exposed to reef decline and coastal erosion driven by climate change, reduction in prey availability, human disturbance, and predation by invasive non‐native species. Using site monitoring data acquired from 2000 to 2023, we investigated drivers of species presence and abundance for 15 seabird species (nine Laridae, three Sulidae, two Fregatidae, and one Procellariidae) on 100 coral reef islands around New Caledonia, South Pacific. We established presence and abundance estimates using a compendium of 2805 observations and tested the relative influence of onsite breeding habitat area, characteristics of neighboring marine environments, human visitation, and rodent presence. Responses to ecological drivers varied across species and highlighted distinct functional and taxonomic groups. The presence and abundance of pelagic‐feeding species with high site fidelity were predominantly determined by the availability of breeding habitat, whereas the presence of coastal foragers, including most gulls and terns, appeared constrained by resource availability near breeding sites. Human disturbance had a significant negative influence on the presence of brown noddy ( Anous stolidus ; [−3.41; −1.20]), masked ( Sula dactylatra ; [−3.85; −1.21]), and brown ( Sula leucogaster ; [−4.57; −1.46]) and red‐footed booby ( Sula sula ; [−9.58; −1.20]) and a significant positive influence on the abundance of the commensal silver gull ( Larus novaehollandiae ; [0.03; 0.09]). Our results emphasize the importance of habitat restoration and mitigation of human disturbance for preserving breeding sites of pelagic‐feeding species. However, it may be difficult to sustain populations of coastal seabirds whose presence is mostly driven by small‐scale prey distribution. Thus, a comprehensive approach that fully considers the functional diversity of target seabird communities is needed.

Integrating borehole image log, core data, and computed tomography for characterizing natural open fractures in the Pre-salt Barra Velha Formation, Santos Basin, Brazil - Luiza de Carvalho Mendes; Gabriela F. Matheus; Ole P. Wennberg; Haili Long-Sanouiller; Mateus Basso; Juan F. Villacreses Morales; Guilherme F. Chinelatto; Alexandre C. Vidal (Journal of Structural Geology, 2026)

The use of convolutional neural networks to predict carbonate dissolution features in acoustic borehole images: an example from brazilian pre-salt reservoirs - Guilherme Furlan Chinelatto; João Paulo da Ponte Souza; Mateus Basso; Alexandre Campane Vidal (Earth Science Informatics, 2026)
The dissolution features in carbonate rocks are common and highly variable; ranging from millimetric pores to enlarged conduits, open fractures, and even caves. Identifying these features is essential in multiple contexts, particularly in the oil industry, as they significantly impact fluid flow capacity and reservoir performance. Furthermore, their identification helps drilling campaigns predict and mitigate zones with high losses of drilling mud. In this context, we propose a novel methodology for identifying dissolution features in carbonate rocks using BHI and CNN models. For this task, seven wells with acoustic BHI from carbonates from Barra Velha Formation located at Santos Basin, Brazil, were used. The proposed workflow includes: (i) defining the display image scale and cut height size (CHS); (ii) class definition and dataset labeling; (iii) CNN model training; and finally (iv) applying the best CNN model to a blind well to check the performance in an untrained dataset. The display resolution of 1:10 was defined and four CHS scenarios were tested: 10 cm (S1), 40 cm (S2), 70 cm (S3) and 100 cm (S4). Six classes were defined based on the type and intensity of dissolution, encompassing a range from non-vuggy rock to facies dominated by vuggy matrix porosity, fracture related dissolution, and large scale conduits or caves. Four CNN models were tested to predict dissolution features: ResNet, RegNet, ShuffleNet, and MobileNet. For scenarios S1 to S3, the ResNet model achieved the best performance, with accuracy values around 0.90 and F1-macro of 0.80. In S4, MobileNet was the best model, with accuracy values close to 0.70 and F1-macro of 0.58. Finally, a qualitative analysis was made using the blind well to evaluate the performance of each model in an untrained/unseen dataset. Although CNN performance decreases with increasing CHS, the results indicate that a multi-scale approach combining 10 cm and 70 cm sample heights provides a robust workflow for capturing both fine-scale dissolution textures and larger-scale geological trends along the wellbore.

Forest transpiration in Brazilian drylands: measurement and validation of a hydrological model - Nazaré Suziane Soares; José Vidal de Figueiredo; Carlos Alexandre Gomes Costa; Italo Sampaio Rodrigues; José Carlos de Araújo (Journal of South American Earth Sciences, 2026)

Therapeutic Drug Monitoring of Itraconazole in Endemic Paracoccidioidomycosis: Real-World Data - Wdson Luis Lima Kruschewsky; Vera Lucia Teixeira de Freitas; Mariane Taborda; Isabela Antonini Alves Oliveira Quadros; Mônica Scarpelli Martinelli Vidal; Tiago Alexandre Cocio; Gil Benard; Nilo José Coêlho Duarte; Vítor Falcão de Oliveira; Adriana Satie Gonçalves Kono Magri; Marcello Mihailenko Chaves Magri (Mycopathologia, 2026)

Variability in the pore structure of microbialites in Lagoa Salgada: Implications for reservoir characterization and petrophysical interpretations - Tales Rodrigues de Almeida; Mateus Basso; Guilherme Furlan Chinelatto; Eddy Ruidiaz Munoz; Alexandre Campane Vidal (Journal of South American Earth Sciences, 2026)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Paleoenvironmental reconstitution of a coastal tropical peatland and its relationship with the Holocene sea level variation (SE Brazil) - André Luiz Miranda Reis; Cynthia Fernandes Pinto da Luz; Ingrid Horák-Terra; Alexandre Christófaro Silva; Plínio Barbosa de Camargo; Pablo Vidal-Torrado (CATENA, 2025)

A synopsis of Senna ser. Bacillares (Leguminosae, Caesalpinioideae, Cassieae) in Brazil, including a remarkable new species from Amazonia - Alexandre Gibau De Lima; Vidal De Freitas Mansano; Marcelo Trovó Lopes De Oliveira; Gwilym Peter Lewis; Christine D. Bacon; Vinicius Castro Souza (Brittonia, 2025)
Senna (Leguminosae, Cassieae) comprises ca. 300 species mainly distributed throughout the Americas. Although the genus is speciose and taxonomically problematic, very few studies have addressed the systematics of Senna in recent years, and many taxonomic and nomenclatural issues remain unresolved. Senna sect. Chamaefistula ser. Bacillares is the most speciose of the American series of Senna and is the most problematic series in the genus. Based on fieldwork and extensive analysis of herbarium collections, we document the occurrence of 29 species of Senna ser. Bacillares in Brazil. This total includes Senna rionegrensis , which is newly described from Amazonia and distinguished by its short abaxial stamens. We provide a synopical treatment of the taxa of Senna ser. Bacillares occurring in Brazil, including identification keys, short morphological descriptions, taxonomic notes, and distributional and phenological data. This work contributes to the taxonomic knowledge of Senna ser. Bacillares in Brazil and serves as a baseline for our ongoing taxonomic revision.

Late 21st‐Century Climate and Land Use Driven Loss of Plant Diversity in African Mountains - João de Deus Vidal Junior; Alexandre Antonelli; Clinton Carbutt; Vincent Ralph Clark; Tobias Fremout; Christopher Chapano; Inês Chelene; David Chuba; Tadesse Woldemariam Gole; Clayton Langa; Benoit Loeuille; Ermias Lulekal Molla; et al. (Global Change Biology, 2025)
With the 1.5°C–5°C increase in global temperature projected for this century, many plant species are expected to shift their distribution ranges to track their environmental requirements. Across several mountain regions, responses to climate change like upslope shifts may result in accelerated rates of species turnover, species richness increases in upper montane belts, and amplified habitat losses. Yet, evidence of how such processes may influence plant diversity in Africa is still scarce. Here, using a species distribution modeling approach, we quantify and map how different scenarios of climatic and land‐use changes may affect plant species ranges in African mountains. Using individually tuned models and dispersal buffers, we compared distribution losses and potential expansion through dispersal across 607 vascular plant species under three shared socioeconomic pathways for the end of the century. Our projections indicate that keeping warming under 2°C until 2100 under a sustainability scenario (SSP1.26), almost half (49.3%) of the species would experience a contraction in suitable areas, compared to 71%–75.6% in case these targets are not met (SSP3.70 and SSP5.85). Among these losses, mean contractions between 19% and 50.4% are predicted depending on the scenario. We project rates of upslope shifts that may be up to three times higher than the global calculated average. Contractions will be higher for species occurring at upper elevations, and trees and shrubs will show lower declines. Our findings align with previously reported trends of upslope shifts of species distributions but suggest that accelerated rates of change may limit the capacity of some species to track their niche based solely on their natural dispersal capacity. This implies that further efforts to improve habitat connectivity, restoration, and assisted migration may be necessary.

A new microwave-assisted synthesis route to produce doped ZnO nanocrystals in non-polar media for the design of IR emissivity modulation devices - Alexandre Da Silva; Guillaume Maurin-Pasturel; Stephen Legall; Cédric Vancaeyzeele; Frédéric Vidal; Laurent Dupont; Pierre-Henri Aubert (Chemical Engineering Journal, 2025)

Geological reservoir characterization tasks based on computer vision techniques - Leticia da Silva Bomfim; Marcus Vinícius Theodoro Soares; Alexandre Campane Vidal; Helio Pedrini (Marine and Petroleum Geology, 2025)

Phenotypic traits and genetic diversity of elephant grass for bioenergy purposes - Josefa Grasiela Silva Santana; Rogério Figueiredo Daher; Moisés Ambrósio; Cleudiane Lopes Leite; Ana Kesia Faria Vidal; Rafael Souza Freitas; Maxwel Rodrigues Nascimento; José Antonio Lamônica Netto; João Victor Bousquet Duarte; João Esdras Calaça Farias; Alexandre Gomes de Souza (Genetic Resources and Crop Evolution, 2025)

Morphometric and taxonomic studies of Senna ser. Coriaceae (Leguminosae, Caesalpinioideae, Cassieae), including a new species from Chapada Diamantina, Bahia, Brazil - Alexandre Gibau de Lima; Vidal de Freitas Mansano; Marcelo Trovó; Christine D. Bacon (Brazilian Journal of Botany, 2024)
Senna sect. Chamaefistula ser. Coriaceae is restricted to Brazil and is predominantly distributed in savanna habitat. The species are morphologically characterized by their shrub or treelet habit, usually reniform stipules, extrafloral nectaries usually positioned on the middle or distal part of the petiole, zygomorphic corolla and laterally compressed fruits with the seeds parallel to the fruit valves. Previous taxonomic studies have recognized only three species and one variety, nevertheless, they provided the groundwork for a more comprehensive treatment, presented here. Based on fieldwork and on the analysis of herbarium specimens, we recognize five species belonging to Senna ser. Coriaceae including one new species from the seasonally dry areas in the Chapada Diamantina, Senna diamantinensis . We carried out a morphometric analyses and here recognize S. caesia as a distinct species rather than a variety of S. corifolia . We propose a new combination for Cassia kuhlmannii and recognize it under the genus Senna . In addition, we propose two first-step lectotypifications and one second-step lectotypification. The taxonomic treatment provided here includes an identification key, morphological descriptions, taxonomic notes, illustrations, preliminary conservation assessments, and habitat and phenology data for each species.

The influence of major faults and fractures on the development of non-matrix porosity system in a pre-salt carbonate reservoir, Santos Basin – Brazil - Luiza de C. Mendes; Mateus Basso; Juan Villacreces Morales; Guilherme F. Chinelatto; Joan Marie Blanco; Ulisses M.C. Correia; João Paulo Ponte; Gabriela F. Matheus; Marilia M. Camargo; Jean Carlos R. Gavidia; Renato S.P.de Medeiros; Alexandre C. Vidal (Journal of Structural Geology, 2024)

Ultrasound-assisted extraction of anthocyanins from grape pomace using acidified water: Assessing total monomeric anthocyanin and specific anthocyanin contents - Betina Louise Angioletti Decker; Elenilson de Godoy Alves Filho; Lorena Mara Alexandre e Silva; Paulo Riceli Vasconcelos Ribeiro; Edy Sousa de Brito; Fabiano André Narciso Fernandes; Thatyane Vidal Fonteles; Sueli Rodrigues (Food Research International, 2024)

Plasmonic Al, Ga and in-doped zinc oxide nanoparticles as key components for the design of electrophoretic inks with MWIR and LWIR absorbance properties - Alexandre Da Silva; Cédric Vancaeyzeele; Frédéric Vidal; Laurent Dupont; Pierre-Henri Aubert (Chemical Engineering Journal, 2024)

Relationships between morphological facies and the evolutionary processes of petroplinthites in the Southern Espinhaço Range (SE-Brazil) - Daniela Schievano de Campos; Danilo de Lima Camêlo; Alexandre Christófaro Silva; Marcilene dos Santos; Pablo Vidal-Torrado (CATENA, 2024)

Residual oil saturation in Pre-salt Brazilian carbonates: A multi-approach core-to-log case study - Ronaldo Herlinger Jr; Leonardo André Fraga Bonzanini; Alexandre Campane Vidal (Journal of South American Earth Sciences, 2024)

Gene flow, mating patterns and inbreeding depression in Roupala montana var. brasiliensis, a neotropical timber species - Fernanda B. Pereira; Alexandre M. Sebbenn; David H. Boshier; Bruno C. Rossini; Celso L. Marino; Miguel L. M. Freitas; João R. B. F. Rosa; Edson Vidal; Evandro V. Tambarussi (New Forests, 2024)

Unravelling the origin of reworked deposits in Aptian lacustrine carbonate reservoirs of the Santos Basin, SE Brazil - Renato Sol Paiva de Medeiros; Mateus Basso; Guilherme F. Chinelatto; Marcus Vinícius Theodoro Soares; Gabriela F. Matheus; Juan Francisco Villacreses Morales; Luiza de Carvalho Mendes; Alexandre Campane Vidal (Marine and Petroleum Geology, 2024)

Adaptability and stability of black bean genotypes with normal and early cycle - Moisés Ambrósio; Rogério Figueiredo Daher; Raiane Mariani Santos; Josefa Grasiela Silva Santana; Ana Kesia Faria Vidal; Maxwel Rodrigues Nascimento; Cleudiane Lopes Leite; Alexandre Gomes de Souza; Rafael Souza Freitas; Wanessa Francesconi Stida; João Esdras Calaça Farias; Benedito Fernandes de Souza Filho; et al. (Euphytica, 2024)

Brominated flame retardants and natural organobrominated compounds in a vulnerable delphinid species along the Brazilian coast - Lara G. Vidal; Nara De Oliveira-Ferreira; João Paulo M. Torres; Alexandre F. Azevedo; Ana Carolina O. Meirelles; Leonardo Flach; Camila Domit; Ana Bernadete L. Fragoso; Flávio J. Lima Silva; Vítor Luz Carvalho; Milton Marcondes; Lupércio A. Barbosa; et al. (Science of The Total Environment, 2023)

Remote sensing of the Earth's soil color in space and time - Rodnei Rizzo; Alexandre M.J.-C. Wadoux; José A.M. Demattê; Budiman Minasny; Vidal Barrón; Eyal Ben-Dor; Nicolas Francos; Igor Savin; Raul Poppiel; Nelida E.Q. Silvero; Fabrício da Silva Terra; Nícolas Augusto Rosin; et al. (Remote Sensing of Environment, 2023)

Pre-salt carbonate cyclicity and depositional environment: NMR petrophysics and Markov cyclicity of lacustrine acoustic facies (Santos Basin, Brazil) - Marcus Vinícius Theodoro Soares; Letícia da Silva Bomfim; Alexandre Campane Vidal; Michelle Chaves Kuroda Avansi; Oton Rúbio Cunha; Richard Guillermo Vásconez García; Renato Sol de Paiva Medeiros (Marine and Petroleum Geology, 2023)

Digital Rock Analysis Based on X-ray Computed Tomography of a Complex Pre-salt Carbonate Reservoir from the Santos Basin, SE Brazil - Gabriela Fernandes Matheus; Mateus Basso; João Paulo da Ponte Souza; Alexandre Campane Vidal (Transport in Porous Media, 2023)

The petrophysical characteristics of Macabu formation (Aptian, Campos Basin) continental carbonates: Core and special well logs (UBI and NMR) analysis integration - Vinicius Gaino Oliveira; Mateus Basso; Guilherme Furlan Chinelatto; Aline Maria Poças Belila; Alexandre Campane Vidal (Journal of South American Earth Sciences, 2023)

Impact of tectonic topographic rejuvenation in landscapes with high bedrock/duricrust strength: Insights from geomorphic evidence in a post-rifted region (SE Brazil) - Daniela Schievano de Campos; Marcilene dos Santos; Karina P.P. Marques; Alexandre Christófaro Silva; Pablo Vidal-Torrado (Geomorphology, 2023)

Seabird and reef conservation must include coral islands - Tristan Berr; Maria P. Dias; Serge Andréfouët; Tammy Davies; Jonathan Handley; Matthieu Le Corre; Alexandre Millon; Éric Vidal (Trends in Ecology & Evolution, 2023)

Towards automatic and accurate core-log processing - Artur Jordao; Joao Paulo da Ponte Souza; Michelle Chaves Kuroda; Marcelo Fagundes de Rezende; Helio Pedrini; Alexandre Campane Vidal (Journal of Applied Geophysics, 2023)

Residual oil saturation investigation in Barra Velha Formation reservoirs from the Santos Basin, Offshore Brazil: A sedimentological approach - Ronaldo Herlinger; Luiz Fernando De Ros; Rodrigo Surmas; Alexandre Vidal (Sedimentary Geology, 2023)

Impact of seismic data conditioning on the identification of structural elements: A case of study from the pre-salt reservoir, Santos Basin, Brazil - Juan Francisco Villacreses Morales; Amir Abbas Babasafari; Guilherme Furlan Chinelatto; Cristian Ricardo Mendoza; Chibuzor David Nworie; Alexandre Campane Vidal (Journal of Applied Geophysics, 2023)

Physiological, epigenetic, and proteomic responses in Pfaffia glomerata growth in vitro under salt stress and 5-azacytidine - Evandro Alexandre Fortini; Diego Silva Batista; Sérgio Heitor Sousa Felipe; Tatiane Dulcineia Silva; Ludmila Nayara Freitas Correia; Letícia Monteiro Farias; Daniele Vidal Faria; Vitor Batista Pinto; Claudete Santa-Catarina; Vanildo Silveira; Clelia De-la-Peña; Eduardo Castillo-Castro; et al. (Protoplasma, 2023)

Genotyping-by-sequencing of passion fruit (Passiflora spp.) generates genomic resources for breeding and systematics - Joshua D. Anderson; Ravena Ferreira Vidal; Maria Brym; Eric T. Stafne; Marcio F. R. Resende; Alexandre Pio Viana; Alan H. Chambers (Genetic Resources and Crop Evolution, 2022)

Simultaneous selection for yield, adaptability and stability and repeatability coefficient in full-sib families of elephant grass for energy purposes via mixed models - Ana Kesia Faria Vidal; Rogério Figueiredo Daher; Rafael Souza Freitas; Wanessa Francesconi Stida; Moisés Ambrósio; Josefa Grasiela Silva Santana; Alexandre Gomes de Souza; Geraldo de Amaral Gravina; Marcelo Vivas; Antônio Teixeira do Amaral Junior (Euphytica, 2022)

Genetic gains in Passiflora for resistance to cowpea aphid-borne mosaic virus using recurrent selection - Débora Souza Mendes; Alexandre Pio Viana; Eileen Azevedo Santos; Natan Ramos Cavalcante; Cleidiane Alves Rodrigues; Joameson Antunes Lima; Ravena Ferreira Vidal; Fernando Henrique de Barros Walter; Luan Baritiello da Silva Bezerra; Marcelo Eiras; Huarrisson Azevedo Santos (Euphytica, 2022)

Acoustic image log facies and well log petrophysical evaluation of the Barra Velha Formation carbonate reservoir from the Santos Basin, offshore Brazil - Mateus Basso; João Paulo Ponte Souza; Bruno César Zanardo Honório; Leandro Hartleben Melani; Guilherme Furlan Chinelatto; Aline Maria Poças Belila; Alexandre Campane Vidal (Carbonates and Evaporites, 2022)

Make flying-fox hunting sustainable again: Comparing expected demographic effectiveness and hunters’ acceptance of more restrictive regulations - Malik Oedin; Fabrice Brescia; Eric Vidal; Alexandre Millon (Ambio, 2022)

Relationship between biofabric and petrophysics in coquinas, insights on Brazilian Barremian–Aptian carbonates of the Santos and Sergipe–Alagoas Basins - Guilherme Furlan Chinelatto; Aline Maria Poças Belila; Mateus Basso; Alexandre Campane Vidal (International Journal of Earth Sciences, 2021)

Sedimentology and petrophysical analysis of pre-salt lacustrine carbonate reservoir from the Santos Basin, southeast Brazil - Mateus Basso; Aline Maria Poças Belila; Guilherme Furlan Chinelatto; João Paulo da Ponte Souza; Alexandre Campane Vidal (International Journal of Earth Sciences, 2021)

Style Transfer applied to CT image downscaling: a study case from Brazilian Coquinas - João Paulo da Ponte Souza; Michelle Chaves Kuroda Avansi; Aline Maria Poças Belila; Alexandre Campane Vidal (Computational Geosciences, 2021)

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Prospecting on Passiflora backcross families: implications for breeding aiming at CABMV resistance - Deurimar Herênio Gonçalves; Alexandre Pio Viana; Eileen Azevedo Santos; Sandra da Costa Preisigke; Ravena Ferreira Vidal; Natan Ramos Cavalcante (Euphytica, 2021)

An update of the Worldwide Integrated Assessment (WIA) on systemic pesticides. Part 4: Alternatives in major cropping systems - Andrea Veres; Kris A. G. Wyckhuys; Jozsef Kiss; Ferenc Tóth; Giovanni Burgio; Xavier Pons; Carlos Avilla; Stefan Vidal; Jaka Razinger; Renata Bazok; Ewa Matyjaszczyk; Ivan Milosavljević; et al. (Environmental Science and Pollution Research, 2020)
We present a synthetic review and expert consultation that assesses the actual risks posed by arthropod pests in four major crops, identifies targets for integrated pest management (IPM) in terms of cultivated land needing pest control and gauges the implementation “readiness” of non-chemical alternatives. Our assessment focuses on the world’s primary target pests for neonicotinoid-based management: western corn rootworm (WCR, Diabrotica virgifera virgifera ) in maize; wireworms ( Agriotes spp.) in maize and winter wheat; bird cherry-oat aphid ( Rhopalosiphum padi ) in winter wheat; brown planthopper (BPH, Nilaparvata lugens ) in rice; cotton aphid ( Aphis gossypii ) and silver-leaf whitefly (SLW, Bemisia tabaci ) in cotton. First, we queried scientific literature databases and consulted experts from different countries in Europe, North America, and Asia about available IPM tools for each crop-pest system. Next, using an online survey, we quantitatively assessed the economic relevance of target pests by compiling country-level records of crop damage, yield impacts, extent of insecticide usage, and “readiness” status of various pest management alternatives (i.e., research, plot-scale validation, grower-uptake). Biological control received considerable scientific attention, while agronomic strategies (e.g., crop rotation), insurance schemes, decision support systems (DSS), and innovative pesticide application modes were listed as key alternatives. Our study identifies opportunities to advance applied research, IPM technology validation, and grower education to halt or drastically reduce our over-reliance on systemic insecticides globally.

Late Quaternary vegetation and climate dynamics in central‐eastern Brazil: insights from a ~35k cal a bp peat record in the Cerrado biome - Ingrid Horák‐Terra; Antonio Martínez Cortizas; Cynthia Fernandes Pinto Da Luz; Alexandre Christófaro Silva; Tim Mighall; Plínio Barbosa De Camargo; Carlos Victor Mendonça‐Filho; Paulo Eduardo De Oliveira; Francisco Willian Cruz; Pablo Vidal‐Torrado (Journal of Quaternary Science, 2020)
The late Quaternary evolution of central‐eastern Brazil has been under‐researched. Questions remain as to the origin of the Cerrado, a highly endangered biome, and other types of vegetation, such as the Capões – small vegetation islands of semi‐deciduous and mountain forests. We investigated the factors that influenced the expansion and contraction of the Cerrado and Capões during the late Quaternary (last ~35 ka), using a multi‐proxy approach: stable isotopes (δ 13 C, δ 15 N), geochemistry, pollen and multivariate statistics derived from a peat core (Pinheiro mire, Serra do Espinhaço Meridional). Five major shifts in precipitation, temperature, vegetation and landscape stability occurred at different timescales. Our study revealed that changes in the South Atlantic Convergence Zone (SACZ) seem to have been coeval with these shifts: from the Late Glacial Maximum to mid‐Holocene the SACZ remained near (~29.6 to ~16.5k cal a bp ) and over (~16.5 to ~6.1 k cal a bp ) the study area, providing humidity to the region. This challenges previous research which suggested that climate was drier for this time period. At present, the Capões are likely to be a remnant of a more humid climate; meanwhile, the Cerrado biome seems to have stablished in the late Holocene, after ~3.1 k cal a bp .

Agricultural diversification reduces the survival period of Sclerotinia sclerotiorum sclerotia - Alexandre Dinnys Roese; Gloria Soriano Vidal; Walmes Marques Zeviani; Anibal de Moraes; Louise Larissa May De Mio (European Journal of Plant Pathology, 2018)

Light quality in plant tissue culture: does it matter? - Diego Silva Batista; Sergio Heitor Sousa Felipe; Tatiane Dulcineia Silva; Kamila Motta de Castro; Talita Cristina Mamedes-Rodrigues; Natane Amaral Miranda; Anyela Marcela Ríos-Ríos; Daniele Vidal Faria; Evandro Alexandre Fortini; Kristhiano Chagas; Gabriela Torres-Silva; Aloisio Xavier; et al. (In Vitro Cellular & Developmental Biology - Plant, 2018)

Genetic conservation of small populations of the endemic tree Swartzia glazioviana (Taub.) Glaz. (Leguminosae) in the Atlantic Forest - Janaína Spoladore; Vidal F. Mansano; Maristerra R. Lemes; Luan C. D. de Freitas; Alexandre M. Sebbenn (Conservation Genetics, 2017)

Modulatory effect of the exudates released by the brown kelp Lessonia spicata on the toxicity of copper in early developmental stages of ecologically related organisms - Alexandre Fellous; Santiago Andrade; Francisco Vidal-Ramirez; Ricardo Calderón; Jessica Beltran; Juan A. Correa (Environmental Science and Pollution Research, 2017)

Effects of untreated and treated oilfield-produced water on seed germination, seedling development, and biomass production of sunflower (Helianthus annuus L.) - Mônica Regina da Costa Marques; Paulo Sérgio Alves de Souza; Michelle Machado Rigo; Alexandre Andrade Cerqueira; Julieta L. de Paiva; Fábio Merçon; Daniel Vidal Perez (Environmental Science and Pollution Research, 2015)

Dopa therapy and action impulsivity: subthreshold error activation and suppression in Parkinson’s disease - Frédérique Fluchère; Manon Deveaux; Borís Burle; Franck Vidal; Wery P. M. van den Wildenberg; Tatiana Witjas; Alexandre Eusebio; Jean-Philippe Azulay; Thierry Hasbroucq (Psychopharmacology, 2015)

Tyms double (2R) and triple repeat (3R) confers risk for human oral squamous cell carcinoma - Alexandre Medeiros Bezerra; Thalita Araújo Sant’Ana; Adriana Vieira Gomes; Aurora Karla de Lacerda Vidal; Maria Tereza Cartaxo Muniz (Molecular Biology Reports, 2014)

Physiological and production response of dairy goats bred in a tropical climate - Priscila Teixeira de Souza; Maria Gorete Flores Salles; Antônio Nélson Lima da Costa; Hilton Alexandre Vidal Carneiro; Leonardo Peres de Souza; Davide Rondina; Airton Alencar de Araújo (International Journal of Biometeorology, 2014)

A multisensory approach to spatial updating: the case of mental rotations - Manuel Vidal; Alexandre Lehmann; Heinrich H. Bülthoff (Experimental Brain Research, 2009)